Alternative Handling of Criminal Acts Through Police Regulation Number 8 Of 2021 Concerning the Handling of Criminal Acts Based on Restorative Justice - Intan Sabrina, Ghia; Lutfi Putri D, Nabilah Syifaa; Dhiva Ananda, Melvin; Aziza, Ulfha; Ramadhina, Shafira; Iskandar, Stevri (Zona Law And Public Administration Indonesia, 2024)
Law functions as a tool for social engineering to create a safe and peaceful society, as posited by Roscoe Pound. Reforming criminal law, including the application of restorative justice, is necessary to align with social dynamics. Restorative justice, which prioritizes recovery over retaliation, involves the offender, the victim, and the community in resolving cases. In Indonesia, this approach is regulated by Police Regulation No. 8 of 2021, aimed at resolving cases at the investigation and preliminary examination stages. This study explores the legal basis and practical regulations of restorative justice, identifying obstacles and solutions for its implementation